A new gas chromatographic method development and validation for the simultaneous determination of ibuprofen and caffeine in bulk and pharmaceutical dosage form - Celine Zambakjian; Amir Alhaj Sakur (SpringerOpen, 2020)
Abstract Background Ibuprofen is a nonsteroidal anti-inflammatory drug (NSAID) that has analgesic, anti-inflammatory, and antipyretic properties. Caffeine is one of the most common adjuvant analgesic drugs which is combined with ibuprofen in commercially available formulations. Combining analgesics offers the possibility of increasing effectiveness without increasing dose and therefore risk. Prescribing ibuprofen and caffeine together is common in clinical practice. This is the first work reporting a new and validated gas chromatographic method for the simultaneous determination of ibuprofen and caffeine in bulk and pharmaceutical dosage form. The separation was performed on a TRB-17 column (30.00 m in length, 0.25-mm ID, and 0.25-μm df). Detection was carried out using a flame ionization detector (FID). Methyl paraben was used as an internal standard. The injection volume was 1 μL with 1:50 split ratio using nitrogen as a carrier gas at a flow rate of 1 mL/min. The oven temperature was programmed at 150 °C for 0.5 min, with a rise of 10 °C/min up to 250 °C. The injector temperature was 280 °C, and the detector temperature was 300 °C. The validation of the method including linearity, range, detection limit (DL), quantitation limit (QL), accuracy, precision, specificity, system suitability, and robustness was carried out utilizing International Conference on Harmonization (ICH) guidelines. Results The retention times of methyl paraben, ibuprofen, and caffeine were 1.687, 2.594, and 4.031 min, respectively. The method was linear in the range of 1000-7000 μg/mL for ibuprofen and 162.5-1137.5 μg/mL for caffeine with a correlation coefficient of 0.9999 for both drugs. The DL was found to be 131.68 μg/mL and 15.74 μg/mL for ibuprofen and caffeine, respectively, whereas QL was found to be 399.02 μg/mL for ibuprofen and 47.68 μg/mL for caffeine. The accuracy of the method was validated by mean percentage recovery, which was found to be in the acceptable range. The precision study results of the new method were less than the maximum allowable limit percentage of relative standard deviation %RSD ≤ 2.0. The specificity was evaluated by the standard edition method, and the results of the recovery data showed that excipients do not affect the accuracy of the proposed method. The results of system suitability and robustness tests were also within the acceptable limits. Conclusion The first reported method for simultaneous determination of ibuprofen and caffeine by gas chromatography in bulk and combined dosage form was carried out in this work. The developed method gave a good separation of the drugs and internal standard. The analytical performance of the method was statistically validated as per ICH guidelines, and satisfactory results were obtained. The proposed method can be easily adopted for the routine analysis of ibuprofen and caffeine.